1976
DOI: 10.1136/bmj.2.6044.1095
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory syncytial virus infection in north-east England.

Abstract: SummaryDuring a period covering four winter epidemics 987 respiratory syncytial (RS) virus infections were identified in the children's wards that served a total population of about 875 000 in north-east England. The incidence of admission to hospital with RS virus infection tended to be twice as high among children in Tyneside as that among children from the rest of the catchment area. The risk of hospital admission with RS virus infection in the first year of life for city children was about 1 in 50. The ris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
38
3

Year Published

1978
1978
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(46 citation statements)
references
References 17 publications
5
38
3
Order By: Relevance
“…The hospitalization rate of 20 per 1000 per year in children younger than 1 year of age found in 1975 [7] by taking specimens from all children admitted to a paediatric ward with a respiratory tract illness in north-east England is approximately 50 % lower than the rate derived from our estimates. However, a substantial increase in rates of hospitalization of infants with bronchiolitis during 1980-96 was also seen in an American study [11].…”
Section: Discussioncontrasting
confidence: 65%
See 1 more Smart Citation
“…The hospitalization rate of 20 per 1000 per year in children younger than 1 year of age found in 1975 [7] by taking specimens from all children admitted to a paediatric ward with a respiratory tract illness in north-east England is approximately 50 % lower than the rate derived from our estimates. However, a substantial increase in rates of hospitalization of infants with bronchiolitis during 1980-96 was also seen in an American study [11].…”
Section: Discussioncontrasting
confidence: 65%
“…In the United Kingdom, Sims et al [7] reported over 25 years ago that the risk of hospital admission with RSV in the first year of life in northeast England was 20 per 1000 per year. More recent UK studies have been undertaken in cohorts of pre-term infants and those with underlying chronic lung disease to determine the potential impact of immunoprophylaxis.…”
Section: Introductionmentioning
confidence: 99%
“…Infection rates for RSV of 68.8/100 children during the first year of life and 82.6/100 during the second year have been observed (16). The incidence of RSV-associated bronchiolitis and pneumonia was highest in 2-to 3-month-old infants, whereas with increasing age, the incidence decreased (36,47). In this study, RSV was detected in over 1,400 respiratory samples over a period of nine consecutive seasons.…”
Section: Discussionmentioning
confidence: 85%
“…Unique representative sequences of each of the eight RSV group A VOL. 47,2009 MOLECULAR EPIDEMIOLOGY OF RSV IN GERMANY 1801 genotypes were included in the phylogenetic analysis. GenBank accession numbers and the year and country of isolation of these sequences are given in Table 2.…”
Section: Methodsmentioning
confidence: 99%
“…Respiratory syncytial (RS) virus inevitably infects all infants, with 1 of every 50 babies born in urban areas becoming sufficiently ill with bronchiolitis or pneumonia to require hospital treatment (Sims et al, 1976). The peak prevalence of severe infection lies between the ages of 6 weeks and 5 months (Gardner, 1973;Parrott et al, 1973), suggesting that maternal IgG persisting in the babies' blood confers little or no protection and perhaps even contributes to disease by interaction with RS virus antigen in the lung (Chanock et al, 1970).…”
Section: Introductionmentioning
confidence: 99%